PECULIAR FEATURES IN STRUCTURAL AND FUNCTIONAL HEART VALUES IN PERSONS WITH VARIOUS LEVELS OF BLOOD PRESSURE - A. V. Tuyev; Y. B. Hovayeva (Российский кардиологический журнал, 2002)
113 healthy subjects with normal blood pressure and 26 patients with essential hypertension (BP 140-159/90-99 mm Hg) were inspected by echocardiography. All subjects were divided into 5 groups according to the blood pressure (BP) level. Diastolic and systolic left ventricular volumes were comparable at subjects with different BP-level. Diastolic and systolic left ventricular walls thickness and left ventricular mass (LVM) were larger in subjects with BP >130/85 mm Hg. Correlation analysis showed that the LVM increase correlated with the increase of systolic and diastolic BP, and with right cardiac cavities and left atrial diameter increase. It was found indirect sighs of left ventricular diastolic function decrease (in normal limits), and smaller systolic left ventricular walls thickening in subjects with BP-level >130/85 mm Hg.